Barriers to product return management in automotive manufacturing firms in Malaysia - Zailani, S.; Govindan, K.; Shaharudin, M.R.; Kuan, E.E.L. (Elsevier, 2017)
The increasing of global warming and depletion of natural resources has become a concern for society, government and industry. There is a growing importance on recovery of used materials and products amongst industry players. The Malaysian government has conducted many green campaigns and provided incentives for some green practices; however, the adoption of product return and recovery management is still low amongst automotive manufacturers. Therefore, it is important to understand the obstacles towards product return adoption so that the countermeasures can be thought of to overcome this situation. The objective of this paper is to investigate the barriers of product return management amongst automotive manufacturing firms in Malaysia. A total of 228 automotive manufacturers and assemblers were identified as the sampling frame, which was selected based on the census sampling method due to the limited sample size of the study. The data was analysed using the Partial Least Squares (PLS) with the measurement model had shown sufficient model fit and the structural model revealed that the data supported the hypothesised model. The large effect size and higher than zero values of the predictive capabilities imply that the model has sufficient variance explained for the predictive capability of the hypotheses testing of the study. Based on the results, this study has found that the resource barrier has a significant effect on the level of adoption of product returns. Specifically, the resource barrier and the extent of the manufacturing return adoption were positively related (β = 0.361, p < 0.01), resource barrier and the extent of the distribution returns (β = 0.252, p < 0.05), and resource barrier and the extent of the customer returns (β = 0.333, p < 0.01). The result reflects that automotive manufacturers have a lack of resources to afford the product return implementation; as a matter of fact, high initial investments in terms of finances, human resources, and time are required for the product return adoption. Other variables of the study, such as the attitudinal and perception barrier, information barrier, and technical barrier, were found to be insignificant with the adoption of product return management. As a conclusion, this study discovered that the resource barrier was the major obstacle that impeded the automotive manufacturers in Malaysia from adopting the product return management. The outcome is expected to help policy makers, manufacturers as well as stakeholders in setting appropriate policies and strategies to improve the product return and recovery management adoption.